Determination of complex reaction mechanisms : analysis of chemical, biological, and genetic networks - Ross, John, 1926-2017 (OUP E-Books., 2005)
Covers the determination of complex reaction mechanisms in chemistry, chemical engineering, biochemistry, biology, biotechnology, and genomics. Topics covered include the pulse method, correlation functions, genetic algorithms, general theory of response methods, prescriptions for oscillatory reactions, and more.